Aerosol measurements by SPEXone on the NASA PACE mission: expected retrieval capabilities. (April 2019) - Hasekamp, Otto P.; Fu, Guangliang; Rusli, Stephanie P.; Wu, Lianghai; Di Noia, Antonio; Brugh, Joost aan de; Landgraf, Jochen; Martijn Smit, J.; Rietjens, Jeroen; van Amerongen, Aaldert
Highlights: We introduce the SPEXone instrument for the NASA PACE mission. We demonstrate that SPEXone has high capability for aerosol retrieval. Polarimetric accuracy is the most important factor determining capability for aerosol retrieval. Having many spectral measurements, it is sufficient to measure at a small number (5) of viewing angles for aerosol retrieval. On the PACE mission, retrieval capability will be further enhanced by combining with HARP-2 and OCI. Abstract: SPEXone is a Multi-Angle Polarimeter instrument that is baselined to fly on the NASA Plankton, Aerosol, Cloud, and ocean Ecosystem (PACE) mission, to be launched in 2022. It will perform hyper-spectral measurements of radiance and polarization in the spectral range 385–770 nm at 5 viewing angles ( ± 57 o, ± 20 o, 0 o ) with high accuracy (0.003) on the Degree of Linear Polarization (DoLP). Based on linear error analysis and retrievals on synthetic data, we conclude that SPEXone has the capability to significantly advance the accuracy of retrievals of optical and microphysical aerosol properties compared to past, present, and planned satellite instruments, as required for better quantification of the effect of aerosols on climate. The products that SPEXone will provide are Aerosol Optical Depth (AOD), Single Scattering Albedo (SSA), Aerosol Layer Height (ALH), effective radius, effective variance, complex refractive index, particle number column for both the fine and coarse mode as well as a shape parameter for the coarse mode. PACE will carry two other instrument: the Ocean Color Instrument (OCI) which is the main instrument and the Hyper-Angular Rainbow Polarimeter-2 (HARP-2). The synergistic use of SPEXone with these instruments will further increase retrieval accuracy, in particular for coarse mode parameters and absorption, and will provide unprecedented capability for aerosol above cloud retrievals.